Unrecognized intraorbital wooden foreign body - Kim, Young Ho (Arch Craniofac Surg, 2018)
Intraorbital wooden foreign bodies may present difficulties in diagnosis due to their radiolucent nature. Delayed recognition and management can cause significant complications. We present a case report that demonstrates these problems and the sequela that can follow. A 56-year-old man presented with a 3-cm laceration in the right upper eyelid, sustained by a slipping accident. After computed tomography (CT) scanning and ophthalmology consultation, which revealed no fractures and suggested only pneumophthalmos, the wound was repaired by a plastic surgery resident. Ten days later, the patient’s eyelid displayed signs of infection including pus discharge. Antibiotics and revisional repair failed to solve the infection. Nearly 2 months after the initial repair, a CT scan revealed a large wooden fragment in the superomedial orbit. Surgical exploration successfully removed the foreign body and inflamed pocket, and the patient healed uneventfully. However, the prolonged intraorbital infection had caused irreversible damage to the superior rectus muscle, with upgaze diplopia persisting 1 year after surgery and only minimal muscle function remaining. We report this case to warn clinicians of the difficulties in early diagnosis of intraorbital wooden foreign bodies and the grave prognosis of delayed management.